PENERAPAN METODOLOGI TOZER DALAM PERENCANAAN STRATEGIS SI/TI PADA SEKOLAH TINGGI TEKNIK MUSI - Andri Wijaya; Arif Aliyanto (Jurnal Sistem Informasi, 2013)
At the present time, each organization is required to have differentiation and innovation in order to increase competitiveness against its competitors and increase profit organization. Higher education is a business organization engaged in services can not be separated from the reach of globalization, competition and the use of information systems and information technology ( IS / IT ) in the business process. Sekolah Tinggi Teknik Musi (STT Musi) is an educational institution in the city of Palembang are already using the IS / IT in its operations, but to do the planning and management of IS / IT is aligned with business strategy and vision is still not optimum. Therefore, to optimize the use of IS / IT is right that supports the business strategy and vision and also to improve the business strategy in the future in line with the vision and mission planning needed SI / IT is mature. Therefore this study will result in a strategic planning model of IS / IT in accordance with the business strategy and vision of the STT Musi. This plan will use the methodology proposed by Tozer and the expected results of this study will address the needs of strategic planning model SI / IT from STT Musi which has been much needed in the face of a very high level of competition at this time with the achievement of measurable results and comprehensive.